Relationship between Degree of Radiological Disability and Degree of Pain in Osteoarthritis at Southeast Sulawesi - Muhammad Rustam; Agussalim Ali; Iis Ainu Rahma; La Ode Alifariki (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Introduction. Osteoarthritis (OA) is a degenerative disease with slow progressive which has a characteristic pathological sign of joint deterioration as a result of biochemical, metabolic, physiological, and pathological changes. Pain is a complaint that is generally felt by people with osteoarthritis and has a different degree in each patient. The purpose of this study determines the correlation between radiological abnormalities staging and pain level with osteoarthritic of the knee joint of Kendari general hospital. Methods. This research is an observational analytic study with cross-sectional approach. Thirty-seven samples were acquired through total sampling. Data were analyzed using the Spearman correlation test (p-value <0,05). Result. The univariate analysis shows that most patients have a moderate radiological abnormality that was 12 (32.43%), and most of the patient have severe pain level that was19 (51.35%). Based on the bivariate statistical test, a positive correlation was obtained between radiological abnormalities staging and pain level with osteoarthritis of knee joint with p=0,000 and r=0,831. Conclusion. There was a significant correlation between radiological abnormalities staging and pain level with osteoarthritis of the knee joint of Kendari general hospital.